Pendampingan Budidaya Sayuran Lokal Khas Rawa di Pekarangan dalam Upaya Peningkatan Keberagaman Konsumsi Pangan Masyarakat di Polder Alabio - Hilda Susanti; Rila Rahma Apriani; Hikma Ellya; Nukhak Nufita Sari; Ronny Mulyawan; Nurlaila Nurlaila (Universitas Lambung Mangkurat, 2023)
The supply of nutritious food through a variety of food consumption is very important in reducing stunting prevalence. Some areas of Hulu Sungai Utara (HSU) Regency are the alabio polder area with high cases of stunting children and unproductive swamp land conditions when flooded with rainwater. This service activity provides a solution in utilizing home yards as a place to cultivate local swamp vegetables that have high nutrition, namely water spinach and water mimosa. The activities carried out include planning, which is done by direct observation and coordination with related stakeholders, then educating about the importance of consuming nutritious vegetables. Training and mentoring were given to 25 residents, the majority of whom were farming mothers. Evaluation was carried out by giving a questionnaire to participants regarding the sustainability of the activity. This activity was able to increase the knowledge and skills of the community in cultivating plants in the yard. The application of semi-hydroponic cultivation techniques of typical swamp vegetables has helped the community in providing vegetables when swamp rice fields are flooded in the rainy season and cannot be planted. Evaluation results showed that 88% of participants were enthusiastic about implementing the training in their daily lives because it suited their needs.